PkM-KDUPIP: PELATIHAN KONDISI FISIK ATLET CABANG OLAHRAGA TERUKUR KOTA TANGERANG - Iwan Hermawan; Fahmy Fachrezzy; Uzizatun Maslikah; Endy Safadilla; Haris Nugroho (Yayasan Education and Social Center, 2022)
Athletes that excel at the provincial, national, and international levels are frequently coached without regard to the issue of physical activity and the creation of physical exercise regimens. The purpose of this study is to ascertain how sports coaches in Tangerang are being physically prepared for the Banten Province. A survey method is used in this investigation. The sports coaches in Tangerang City served as the study's sample. Descriptive analysis is the method of data analysis employed in this study. Performing community service through the Partnership Program for the Business World, Local Government, and Educational Agencies (PkM-KDUPIP) about physical condition training in the Tangerang City Measurable Sports Branch to get ready for the 2022 Banten Province Porprov will help trainers realize the value of physical activity and help them create physical activity programs. To formulate and create training programs appropriate to the goals or objectives in the 2022 Porprov, achieve optimal performance, and at the same time make the City of Tangerang the General Champion in the Banten Province 2022, all those involved in this training must undergo a thorough debriefing. The profile of the physical condition includes the following measurements: (1) Anthropometric test, which measures height (in centimeters) and body weight (in kilograms); (2) Test of Biomotor Ability or Physical Ability, which measures flexibility with units of centimeters; (3) Explosive power test of the leg muscles using the Vertical Jump with a unit of assessment in centimeters; and (4) Abdominal muscle strength test using Push-ups with a unit of measurement for the number of repetitions in one minute